The Effect of Web-based Inquiry Physics Problems on High School Students' Physics Learning Outcomes - Herliana, Fitria; Mardila, Rini; Mahzum, Elmi; Zainuddin, Zainuddin; Wahyuni, Agus; Elisa, Elisa; Muliyati, Dewi (Universitas Muhammadiyah Makassar, 2025)
Physics learning in high schools often faces challenges due to students' low conceptual understanding of abstract topics like sound waves. To address this challenge, this study investigates the effectiveness of Web-based Inquiry Physics Problems (WIPPer), an innovative learning platform that incorporates a problem-based learning approach within a blended learning framework. Using a pre-experimental one-group pretest-posttest design, the research was conducted on 20 eleventh-grade students at State Senior High School 2 Kuta Baro. Data were collected through a learning outcome test comprising 10 multiple-choice items (cognitive levels C1–C4), teacher and student response questionnaires, and observation sheets to monitor engagement throughout the WIPPer implementation. The results showed a medium average N-gain of 0.5116, with 70% of students achieving medium to high improvement categories. Observational analysis demonstrated 89% effectiveness across all learning phases. Teacher responses rated WIPPer as excellent (media: 93.33%, material and evaluation: 100%), while student responses were also highly favorable (media: 86.16%, material: 93.4%, evaluation: 90%). Cross-tabulation analysis revealed a strong correlation between student engagement and achievement, particularly in analytical activities. Students with high engagement demonstrated better ability in answering complex concept application questions (75.76%) compared to students with low engagement (16.67%). The novelty of this research lies in the integration of gradual assessment, virtual laboratory simulations, and adaptive feedback within a problem-oriented digital platform. This research concludes that WIPPer is a feasible and effective tool that enhances learning outcomes by fostering engagement and supporting independent learning. This research contributes to physics education by presenting WIPPer as a feasible and effective model that aligns with digital learning trends and supports the development of adaptive, student-centered instructional approaches.